History of Logo - Solomon, C; Harvey, B; Kahn, K; Lieberman, H; Miller, M; Minsky, M; Papert, A; Silverman, B (Association for Computing Machinery, 2020)
Logo is more than a programming language. It is a learning environment where children explore mathematical ideas and create projects of their own design. Logo, the first computer language explicitly designed for children, was invented by Seymour Papert, Wallace Feurzeig, Daniel Bobrow, and Cynthia Solomon in 1966 at Bolt, Beranek and Newman, Inc. (BBN).